Autoimmunity against laminin 332 - Patzelt, Sabrina; Schmidt, Enno (Frontiers in Immunology, 2023)
Laminin 332 is a heterotrimeric structural protein of the basal membrane zone (BMZ) of the skin and adjacent mucosal tissues. The importance of laminin 332 for the structural integrity of the BMZ is demonstrated by mutations in any of the three genes encoding for its three chains causing variants of junctional epidermolysis bullosa. Autoimmunity against laminin 332 is observed in mucous membrane pemphigoid (MMP) and in the rare patients with orf-induced pemphigoid. MMP is an autoimmune blistering disease with predominant mucosal manifestations and autoantibodies against the BMZ of the skin and orifice-close mucous membranes. The main autoantigens of MMP are type XVII collagen (BP180) and laminin 332 targeted in about 80% and 10-20% of patients, respectively. An increasing number of studies has highlighted the association of anti-laminin 332 MMP and malignancies that can be revealed in about a quarter of these patients. This data has led to the recommendation of current guidelines to assay for anti-laminin 332 reactivity in all MMP patients. The present review focuses on anti-laminin 332 MMP describing clinical features, its pathophysiology, and detection of serum anti-laminin 332 IgG. In addition, the available data about the occurrence of malignancies in anti-laminin 332 MMP, the underlying tumor entities, and its biology are detailed.